A study of Information and Communication Technology Self-Efficacy, Motivation, Attitude and Barriers towards Online Professional Development among University English Teachers in Ningxia, China - Kong, Ling Di (2018)
The advancement of information and communication technology (ICT) should create a favorable platform for teachers to continue their professional development previous studies have shown that online professional development (OPD) is one of the ways to improve teachers’ development. However, studies showed that the involvement of OPD in China was still unsatisfactory. Therefore, the objective of this study was to examine the relationship between teachers’ ICT self-efficacy, motivation and attitude towards OPD and to explore the barriers impeding teachers’ involvement in OPD. A combination of quantitative and qualitative approach was adopted by using survey questionnaire among 216 university English teachers in Ningxia and semi-structured interviews among eight respondents in Ningxia. SPSS 22 was used for descriptive statistics and data screening. SmartPLS 3 was used to test the relationship among variables, hypotheses and the validity and reliability of the instruments. Interviews data were analyzed using Nvivo 10 which was used to assist the thematic analysis process. The quantitative results showed a moderate level of ICT self-efficacy, motivation and attitude towards OPD. The results also revealed a positive and significant relationship between ICT self-efficacy and attitude towards OPD; however, motivation could not function well to moderate the relationship between ICT self-efficacy and attitude towards OPD. The qualitative findings revealed that situational, dispositional, self-efficacy and institutional barriers were the main themes impeding teachers’ involvement in OPD; meanwhile, family commitment, heavy workload, lack of awareness, deficiency in ICT skills, shortage of preparation time and lack of administrative support were the main sub themes hindering their involvement in OPD. This study suggests that there is a need to reduce teachers’ workload and provide them with adequate technical support as well as to add more courses on ICT skills and to emphasize the quality of OPD courses. Online professional development, Attitude, ICT self-efficacy, Motivation, Chinese university EFL teachers.